STEAM'S APPROACH TO PRIMARY SCHOOL THEMATIC LEARNING - Jicardo Jicardo; Rochmiyati Rochmiyati (Jurnal Ilmiah Teunuleh, 2021)
This research aims to provide information on the application of STEAM approach to primary school thematic learning. The application of STEAM approach includes aspects of learning planning, application of learning, and assessment of STEAM learning in primary school thematic learning. Qualitative approach with this type of case study research through observation. The data of the research results are processed with narrative through observation and verification techniques steps to produce credible conclusions. from these results it is known that STEAM's approach to primary school thematic learning has constraints in its application.